2016
DOI: 10.4314/sajas.v46i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal contamination in raw milk for human consumption

Abstract: The presence of heavy metals in various farm inputs, including feed, fertilizer, water and environment leads to excretion of the residues in animals' milk. Because consumption of milk contaminated with heavy metals poses serious threats to consumers' health, a study was conducted in 2012 -2013 in Pakistan to evaluate the concentration of heavy metals in unprocessed raw milk procured in different seasons from Jhang city, Punjab, Pakistan. A total of 400 milk samples was collected from milk shops and dairy farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Apart from contaminating the environment, heavy metals are also consumed in water and feeds that are eaten by food producing animals, which poses health threats to consumers. 121 It was found that the average concentrations of Cu, Pb, and Cd in raw milk were significantly higher than the International Dairy Federation standards, showing that more active heavy metal surveillance in animal products is required. 121 Similarly, a study from Nigeria showed chicken bone-muscles with concentrations of 28.23 mg/kg for Pb, 16.17 mg/kg for Zn and 4.27 mg/kg for Ni, while chicken brain had the highest levels of Cd and Mg (0.38 and 67.54 mg/kg, respectively).…”
Section: Toxicity Of Heavy Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Apart from contaminating the environment, heavy metals are also consumed in water and feeds that are eaten by food producing animals, which poses health threats to consumers. 121 It was found that the average concentrations of Cu, Pb, and Cd in raw milk were significantly higher than the International Dairy Federation standards, showing that more active heavy metal surveillance in animal products is required. 121 Similarly, a study from Nigeria showed chicken bone-muscles with concentrations of 28.23 mg/kg for Pb, 16.17 mg/kg for Zn and 4.27 mg/kg for Ni, while chicken brain had the highest levels of Cd and Mg (0.38 and 67.54 mg/kg, respectively).…”
Section: Toxicity Of Heavy Metalsmentioning
confidence: 98%
“… 121 It was found that the average concentrations of Cu, Pb, and Cd in raw milk were significantly higher than the International Dairy Federation standards, showing that more active heavy metal surveillance in animal products is required. 121 Similarly, a study from Nigeria showed chicken bone-muscles with concentrations of 28.23 mg/kg for Pb, 16.17 mg/kg for Zn and 4.27 mg/kg for Ni, while chicken brain had the highest levels of Cd and Mg (0.38 and 67.54 mg/kg, respectively). 122 These results show that both Pb and Cd should be of great concern in Nigeria due to the contamination of meat and vegetables.…”
Section: Toxicity Of Heavy Metalsmentioning
confidence: 98%
“…As a matter of fact, in the study carried out in order to determine the seasonal (summer and winter) and change of some element levels of 400 milk samples according to their place of origin in Pakistan. Especially Pb levels (0.455 mg / kg in summer; 2.0 mg / kg in winter) at the point of sale and milk obtained in winter were higher than Pb values of samples taken from canal edge farms (0.227 mg / kg in summer; 1.25 mg / kg in winter) (Younus et al, 2016). Among a total of 260 conventional milk samples (130 in summer and 130 in winter) collected from Van province and its surroundings, Pb was found in 189 samples with the mean value of 0.002 ± 0.01 ppm (0.001 -0.007).…”
Section: Resultsmentioning
confidence: 67%
“…Moreover, several metals have emerged as human carcinogens (Farahmandkia et al, ed with metals, drinking water from contaminated sources and even the dust that settles on the grass that the animal consumes (Amponsah, 2014). The presence of heavy metals in various farm inputs, including feed, fertilizer, water and environment leads to excretion of the residues in animal's milk (Younus et al, 2016). Heavy metals accumulate in tissues of dairy animals and ultimately excrete in milk because of their non-biodegradable and persistent nature (Burger and Elbin, 2015).…”
Section: Introductionmentioning
confidence: 99%